EFFECTIVENESS OF FINGER LEAF INFUSION (Psophocarpus tetragonolobus (L.) DC) ON THE MALARIA MODEL OF RATS (Rattus norvegicus) - Kaihena, Martha; Samson, Efraim (Universitas Pattimura, 2019)
Winged bean is a type of plant that is used as traditional medicine. This study aims to determine the effectiveness of winged bean leaf infusion (Psophocarpus tetragonolobus(L.) DC) against white rat (Rattus norvegicus) model of malaria. The method used in this research is completely randomized design with 4 treatment groups and 3 replications consisting of a control group without being given an infusion (P1), a group that was given an infusion of concentrations: 31.25 mg/mL (P2), 62.5 mg/ mL(P3), and 125 mg/mL (P4). This study used 20 male rats, of which 5 rats including as donor mice. Donor mice were infected with Plasmodium berghe and left until the parasitemia percentage reached> 20%. Then 4 groups of model mice were infected with Plasmodium berghei. Observations were made for 7 days, starting from day 0 (before treatment), 4 days during treatment and 2 days after treatment. The percentage of parasitemia was calculated starting from the day before administration of winged bean leaf infusion (IDK) until the 7th day. The results of this study indicate that IDK can inhibit parasite growth by reducing the level of parasitemia along with increasing concentrations, namely (P2) of 73.78%; (P3) of 89.33%; and (P4) of 93.69%. It can be concluded has potential in inhibiting the growth of Plasmodium berghei in the rat model of malaria with an effective concentration of 31.25 mg/mL.